EFEKTIVITAS MODEL PROBLEM BASED LEARNING TERHADAP HASIL BELAJAR IPS MATERI KEKAYAAN BUDAYA INDONESIA SISWA KELAS IV SD - Tri Febrianto, Priyono; Novia Safitri, Narulita; Fahmi Amrullah, Muhammad; Reftamey, Cinta; Rifatil Badri, Zafirah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The primary catalyst for this study is the consistently low level of student learning outcomes in Social Studies, specifically concerning the topic of Indonesian cultural diversity. This educational gap is generally attributed to the prevalence of teacher-centered instructional approaches, which often restrict students’ active engagement throughout the learning process. Consequently, this study aims to evaluate the effectiveness of the Problem Based Learning (PBL) model in enhancing the learning achievements of elementary school students.To achieve this, the research utilized a literature review method by analyzing relevant scientific articles published between 2022 and 2026. Data were gathered through extensive academic literature searches and subsequently analyzed using a descriptive qualitative approach, complemented by thematic analysis techniques.The findings clearly indicate that the implementation of PBL has a significant positive impact on student outcomes, encompassing cognitive achievement, learning motivation, and critical thinking skills. Furthermore, PBL actively encourages student participation through contextual problem-solving activities that are directly related to real-life situations.However, its practical application still faces several notable challenges, such as limited instructional time and the varying levels of teacher readiness in designing and managing a problem-based curriculum. In conclusion, the Problem Based Learning model is highly effective for Social Studies instruction in elementary schools, particularly when it is supported by thorough instructional planning and strong teacher preparedness.